The climate change, biodiversity and nutrition nexus - Hunter, Danny (2024)
Presented at the Anticipatory Climate Change Adaptation: ClimBer Learning Exchange Conference in Manila, Philippines, between 28-29 October 2024. This presentation explores the role of school meals in driving transformation within food systems, highlighting the importance of planet-friendly school meals.